2014
DOI: 10.5152/tjg.2014.3994
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharidase activity in children with inflammatory bowel disease

Abstract: Background/Aims: The etiopathogenesis of inflammatory bowel disease (IBD) is multifactorial and not well explained. Environmental, genetic, and dietary factors play an important role. The aim of the study was the evaluation of lactase, saccharase, and maltase activity in patients with IBD. Materials and Methods: The study comprised 65 children, aged 3-18 years. During a routine endoscopy, we took biopsies from the descending part of the duodenum. In these biopsies, we determined disaccharidase activity using D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…The difference in prevalence of insufficient lactase production in the patients with and without LC and EGID could indicate that there was an association between these two conditions and insufficient lactase production, as found in other studies . Thus, it seems important to screen for lactase deficiency in LC and EGID, as some cases may be linked to lactase deficiency, primary or acquired, and may be treated effectively by a lactose‐free diet .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The difference in prevalence of insufficient lactase production in the patients with and without LC and EGID could indicate that there was an association between these two conditions and insufficient lactase production, as found in other studies . Thus, it seems important to screen for lactase deficiency in LC and EGID, as some cases may be linked to lactase deficiency, primary or acquired, and may be treated effectively by a lactose‐free diet .…”
Section: Discussionmentioning
confidence: 64%
“…Of the 58 patients who underwent endoscopy and did not have LC or EGID, 29 had enzyme activity tests and these revealed seven (24.1%) cases of lactase deficiency. Genetically determined adult‐type hypolactasia was excluded in all but one case and thus lactase deficiency seemed secondary to small bowel pathology .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have some important findings to report, among which and the most important, is that for the first time, a possible link between lactase deficiency and lymphocytic colitis has been identified, and the implications derived from this observation cannot be understated. Of note, a recent report by Wiecek et al seems to support this observation [25], which came to our attention since the article was first drafted.…”
Section: Introductionmentioning
confidence: 64%
“…Strikingly, a 2012 study by Treem also found constipation to be a common presenting complaint, although the pathophysiology of this presentation was not explained 12 . While disaccharidase deficiencies have been implicated in many other gastrointestinal disorders [21][22][23][24] , their existence in patients with IBS-like symptoms remains unclear. Moreover, some patients with disaccharidase deficiencies did not have resolution of these IBS-like symptoms despite appropriate treatment for their deficiency 5 .…”
Section: Introductionmentioning
confidence: 99%